AB0065 Elevated Serum and Synovial Fluid Levels of Tumor Necrosis Factor-Like Ligand 1A and Decoy Receptor 3 in Rheumatoid Arthritis: Induce Interleukin-17 Production. (10th June 2014) - Shen, H.; Xiu, Z.; Tian, Y.; Xia, L.; Lu, J.
Abstract : Background: Tumor necrosis factor superfamily (TNFSF) and their receptors involve in the pathogenesis of Rheumatoid arthritis (RA) (1). TNF-like ligand 1A (TL1A), a member of the TNFSF, can be secreted by endothelial cells, dendritic cells, and lymphocytes (2). The receptor for TL1A is death-domain receptor 3 (DR3), which is predominantly expressed on activated lymphocytes (3). TL1A-DR3 signaling can also promote the secretion of IL-17 and regulate the Th17 mediated autoimmune diseases (4). Decoy receptor 3 (DcR3) belongs to TNF receptor (TNFR) superfamily. DcR3 is a secreted protein which lacks the trans-membrane and cytoplasmic domains. DcR3 can inhibit the function of TL1A-DR3 by compete for the binding of TL1A (5). Therefore, we hypothesized that TL1A-DR3 signaling may be involved in the development of RA by activating Th17 cell function. Objectives: In the present study, we analyzed serum and synovial fluid (SF) levels of TL1A and DcR3 in patients with RA, osteoarthritis (OA) and healthy controls. Moreover, we showed for the first time that TL1A can induce the production of IL-17 by activated peripheral blood mononuclear cells (PBMC) from patients with RA. Methods: The serum and SF levels of TL1A and DcR3, and the production of IL-17 by rhTL1A-treated PBMC were measured by enzyme-linked immunosorbent assay (ELISA). We also tested the change of TL1A and DcR3 level following TNF-α blockade therapy. Results: Serum TL1A and DcR3 levels were higher in RA patients. This increase was more significant in RF and anti-CCP positive patients. TL1A and DcR3 levels were higher in SF samples than in paired sera. TL1A and DcR3 decreased after anti-TNF treatment. rhTL1A increased the production of IL-17. Conclusions: TL1A and DcR3 may be of pathogenic and potentially of therapeutic importance in RA patients. References: McInnes IB, Schett G. Cytokines in the pathogenesis of rheumatoid arthritis. Nat Rev Immunol. 2007 Jun;7(6):429-42. Cassatella MA, Pereira-da-Silva G, Tinazzi I, Facchetti F, Scapini P, Calzetti F, et al. Soluble TNF-like cytokine (TL1A) production by immune complexes stimulated monocytes in rheumatoid arthritis. J Immunol. 2007 Jun 1;178(11):7325-33. Screaton GR, Xu XN, Olsen AL, Cowper AE, Tan R, McMichael AJ, et al. LARD: a new lymphoid-specific death domain containing receptor regulated by alternative pre-mRNA splicing. Proc Natl Acad Sci U S A. 1997 Apr 29;94(9):4615-9. Jones GW, Stumhofer JS, Foster T, Twohig JP, Hertzog P, Topley N, et al. Naive and activated T cells display differential responsiveness to TL1A that affects Th17 generation, maintenance, and proliferation. FASEB J. 2011 Jan;25(1):409-19. Lin WW, Hsieh SL. Decoy receptor 3: a pleiotropic immunomodulator and biomarker for inflammatory diseases, autoimmune diseases and cancer. Biochem Pharmacol. 2011 Apr 1;81(7):838-47. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1415